The epidemiology of AmpC-producing Escherichia coli isolated from dairy cattle faeces on pasture-fed farms. Issue 10 (21st October 2021) - Burgess, Sara A.; Cookson, Adrian L.; Brousse, Lisa; Ortolani, Enrico; Benschop, Jackie; Akhter, Rukhshana; Brightwell, Gale; McDougall, Scott
Abstract : Introduction. Antibiotic use, particularly amoxicillin-clavulanic acid in dairy farming, has been associated with an increased incidence of AmpC-hyperproducing Escherichia coli . Gap statement. There is limited information on the incidence of AmpC-hyperproducing E. coli from seasonal pasture-fed dairy farms. Aim. We undertook a New Zealand wide cross-sectional study to determine the prevalence of AmpC-producing E. coli carried by dairy cattle. Methodology. Paddock faeces were sampled from twenty-six dairy farms and were processed for the selective growth of both extended-spectrum beta-lactamase (ESBL)- and AmpC-producing E. coli . Whole genome sequence analysis was carried out on 35 AmpC-producing E. coli . Results. No ESBL- or plasmid mediated AmpC-producing E. coli were detected, but seven farms were positive for chromosomal mediated AmpC-hyperproducing E. coli . These seven farms were associated with a higher usage of injectable amoxicillin antibiotics. Whole genome sequence analysis of the AmpC-producing E. coli demonstrated that the same strain (<3 SNPs difference) of E. coli ST5729 was shared between cows on a single farm. Similarly, the same strain (≤15 SNPs difference) of E. coli ST8977 was shared across two farms (separated by approximately 425 km). Conclusion. These results infer that both cow-to-cow and farm-to-farm transmission of AmpC-producing E. coli has occurred.